Pengetahuan Perawat Tentang Gangguan Jiwa Dengan Kemampuan Deteksi Dini Gangguan Jiwa - Hafni Van Gobel; Gusti Ayu Putu Putri Ariani; Mohamad Putra Darmawan (Poltekkes Kemenkes Gorontalo, 2021)
Background: Mental health services are no longer focused on efforts to heal clients alone, but also mental health education efforts or prevention efforts with targets other than healthy individual mental disorder clients as preventive efforts. Preventive efforts in this case are through early detection of mental disorders carried out by health workers in this case nurses.Objective: This study aims to determine the knowledge of nurses about mental disorders with the ability to detect mental disorders early.Methods: The study used a quantitative descriptive design. The sample is 17 nurses who work in outpatient polyclinics. The sampling technique used the total sampling method.Results: Based on the results of the study, it was obtained that nurses' knowledge about mental health was still lacking with 10 respondents (58.8%), the ability to detect mental disorders early in the less category nurses amounted to 11 people (64.7%)Conclusion: There is a relationship between nurses' knowledge about mental disorders and the ability to detect mental disorders at the Puskesmas Kota Tengah Gorontalo City.